Gaily the Troubadour Touch'd His Guitar - Bayly, Thomas Haynes (New York: Geib & Walker, 1820)
This song was written in the 1820s by English songwriter and dramatist, Thomas Haynes Bayly (1797-1839), whose other songs include Long, Long Ago. It was popular in both England and America.
Gaily the troubadour touched his guitar, When he was hast'ning home from the war. Singing from Palestine hither I come; Lady love, lady love welcome me home. Singing from Palestine hither I come; Lady love, lady love welcome me home She, for the troubadour hopelessly wept, Sadly she thought of him when others slept. Singing in search of thee would I might roam; Troubadour, troubadour come to thy home. Singing in search of thee would I might roam; Troubadour, troubadour come to thy home. Hark! 'twas the troubadour breathing her name; Under the battlement softly he came. Singing, from Palestine, hither I come; Lady love, lady love, welcome me home. Singing from Palestine hither I come; Lady love, lady love welcome me home